Three-dimensional biomodel in the treatment of bilateral mandibular fracture sequelae: a case report (Research, Society and Development, 2021)
Mandibular fractures lead to changes in occlusion, aesthetic deformities and functional alterations, when untreated, their sequelae may cause permanent problems, leading to a more complex treatment than the acute trauma. The treatment offers challenges that can be minimized with the aid of biomodels, printed by 3D technology. This article aims to report a biomodel-assisted surgical procedure for mandibular reconstruction, arguing how these prototypes may help to achieve better outcomes. The patient was involved in an automobile accident and sought treatment for the sequelae of mandibular fractures two years after the initial trauma. The biomodel printing of her mandible allowed for the execution of surgery on the model, reestablishing correct occlusion and facial aesthetics, and helping shorten the surgical time through the pre-bending of reconstruction plates. The patient improved uneventfully. The use of biomodels must be encouraged, especially in cases where the patient shows sequelae, when the anatomical landmarks are compromised, they offer more predictability for treatment outcomes, as described on this case report.